Nonacog gamma, a novel recombinant factor IX with low factor IXa content for treatment and prophylaxis of bleeding episodes. Issue 2 (March 2015) - Turecek, Peter L; Abbühl, Brigitt; Tangada, Srilatha D; Chapman, Miranda; Gritsch, Herbert; Rottensteiner, Hanspeter; Schrenk, Gerald; Mitterer, Artur; Dietrich, Barbara; Höllriegl, Werner; Schiviz, Alexandra; Horling, Frank; et al.
<x xml:space="preserve">Abstract</x> Nonacog gamma is a new recombinant factor IX to treat factor IX deficiency. It is indicated for control of bleeding episodes, perioperative management and routine prophylaxis to prevent or reduce the frequency of bleeding episodes in adults and children with hemophilia B. Nonacog gamma was first approved in the USA in June 2013 under the trade name RIXUBIS followed by market approvals in Australia and the EU in 2014, and marketing authorization decision is pending in Japan. Nonacog gamma is derived from a recombinant Chinese hamster ovary cell line using a state of the art biotechnological manufacturing process. Recombinant factor IX is produced by Baxter's protein-free fermentation technology, which was first developed for ADVATE. The product is purified and formulated in the absence of any human or animal-derived protein. Nonacog gamma was characterized both in comprehensive in vitro and in vivo non-clinical studies as well as in an extensive clinical trial program.